2021
DOI: 10.1038/s41525-021-00218-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic discrimination: introducing the Asian perspective to the debate

Abstract: Our article aims to provide a comprehensive portrayal of how seven Asian jurisdictions have sought to address the challenge of genetic discrimination (GD) by presenting an analysis of the relevant legislation, policies, and practices. Based on our findings, policy discussion and action on preventing or mitigating GD have been narrowly framed in terms of employment, insurance, disability, marriage, and family planning. Except for South Korea, none of the jurisdictions we examined has adopted specific legislatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…It is of utmost importance to eliminate the root causes of stigmatization and discrimination of the RD population in order to improve social inclusion and reduce opportunities and productivity loss. This can be done through the implementation of anti-discrimination policies such as Genetic Information Nondiscrimination Act (GINA) in the United States to aid assimilation of the RD population into society ( 143 , 144 ). Legislations in Japan and Taiwan have also incorporated social care services into their RD framework, thereby facilitating the inclusion and integration of the RD population into the society in addition to providing quality healthcare ( 145 ).…”
Section: Future Directions Of Rdsmentioning
confidence: 99%
“…It is of utmost importance to eliminate the root causes of stigmatization and discrimination of the RD population in order to improve social inclusion and reduce opportunities and productivity loss. This can be done through the implementation of anti-discrimination policies such as Genetic Information Nondiscrimination Act (GINA) in the United States to aid assimilation of the RD population into society ( 143 , 144 ). Legislations in Japan and Taiwan have also incorporated social care services into their RD framework, thereby facilitating the inclusion and integration of the RD population into the society in addition to providing quality healthcare ( 145 ).…”
Section: Future Directions Of Rdsmentioning
confidence: 99%
“…FMs had concerns about being treated unfavorably based on genetic characteristics, while there are no laws or regulations against genetic discrimination in Japan [14,15]. Several studies showed despite the implementation of The Genetic Information Nondiscrimination Act (GINA) in the US, low awareness and insufficient understanding persists [16,17]; even in a survey conducted 10 years later, the respondents answered incorrectly and indicated that they would refuse genetic testing due to fairness of discrimination in employment and insurance [18].…”
mentioning
confidence: 99%
“…Management of heterozygous FH is aimed at primary prevention of atherosclerotic cardiovascular disease through lipid lowering pharmacological therapy, using statins, ezetimibe or PCSK9 inhibitors or other LDL lowering medications, with guidelines recommending initiation at ages 8–10 or earlier based on severity ( Carroll et al, 2008 ; Gidding et al, 2015 ; Defesche et al, 2017 ; Kim et al, 2021 ). Trials have yet to directly compare cardiovascular disease outcomes associated with different pharmacologic treatments for heterozygous FH, and treatment recommendations therefore are based on surrogate outcomes including LDL cholesterol lowering and arterial imaging ( Defesche et al, 2017 ).…”
Section: Are There Accepted Options For Surveillance and Prevention F...mentioning
confidence: 99%
“…Barriers for screening participation include cost, genetic discrimination, test accuracy, and data confidentiality ( Ten Haaf et al, 2017 ). Genetic discrimination, particularly in the context of insurance, employment, and social relationships ( Wauters and Van Hoyweghen, 2016 ), remains a pervasive deterrent to screening amongst the public, despite the existence of policies to protect sensitive genetic information from misuse worldwide ( Joly et al, 2017 ; Kim et al, 2021 ).…”
Section: Is the Test Acceptable To The Population?mentioning
confidence: 99%